Evaluation of an enhanced ultrasonic-assisted biodiesel synthesized using safflower oil in a diesel power generator. Issue 4 (18th May 2020) - Hosseinzadeh Samani, Bahram; Ansari Samani, Marzieh; Shirneshan, Alireza; Fayyazi, Ebrahim; Najafi, Gholamhassan; Rostami, Sajad
Abstract: Given the energy crisis, fossil fuel reserves crisis, climate mitigation, and energy efficiency increase, scientists have embarked on producing alternative fuels such as the biodiesel. This study was conducted to investigate the feasibility of biodiesel production from safflower oil using the ultrasonic system, and to evaluate the produced fuel using a diesel power generator. In this study, the effects of alcohol-to-oil molar ratio, ultrasound power (W), catalyst concentration (w/w %), and the reaction time (min) on methyl ester yield were investigated. By increasing the molar ratio to a point between the ratios 4:1 and 6:1, the conversion rate first increases 11.42%, and then it remains unchanged from the point 6 to 8. As the ultrasonic power increases, the rate of conversion increases incrementally. The optimization was obtained at 7.02 molar ratio, 160 W ultrasound power, 0.95 (w/w%) catalyst concentration, and 8.47 min reaction time. The results showed that the brake torque and broke power increased when the amount of biodiesel in fuel increased from B0 to B50. The results showed that CO emissions decreased and NOx increased when there was an increase of amount of biodiesel.